PENERAPAN METODE GAME’S UNTUK MENINGKATKAN KARAKTER PADA SISWA SEKOLAH DASAR - Delia Putri; Elvina Elvina (STKIP ROKANIA, 2019)
This study aims to improve the character of students at SDN 006 Rambah by applying the game's method. This type of research is action research with qualitative and quantitative methods. The instrument used was a student observation sheet. The results of the study on listening to the first cycle of listening skills are in the poor category, which is 65%. Furthermore, in the second cycle the average student activity is in the sufficient category, which is 60%. In learning writing skills the first cycle on average is in the sufficient category, which is 65%. Then in cycle II the average student activity is in the good category, which is 85%. In learning the speaking skills of the first cycle the average is in the sufficient category, which is 70%. Then in cycle II the average student activity is in the good category, which is 90%. In learning the first cycle reading skills are in the average category, which is 50%. Furthermore, in cycle II the average student activity is in the very good category, which is 60%. It was concluded that the application of the game's method could improve student character, especially in SDN 006 Rambah. Character values ​​that can be improved in students in the language skills learning process, including the character values ​​of cooperation, discipline, and honesty.